2021
DOI: 10.1111/2041-210x.13606
|View full text |Cite
|
Sign up to set email alerts
|

Neural ordinary differential equations for ecological and evolutionary time‐series analysis

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(47 citation statements)
references
References 47 publications
0
47
0
Order By: Relevance
“…Valuable effort would therefore be expended in future work to consider the relationship of model flexibility to the parametric-and structural sensitivities of models when it comes to drawing inferences for population dynamics (e.g., Aldebert and Stouffer, 2018;Adamson and Morozov, 2020). Likewise, it would also be useful to clarify the relevance of model flexibility to the rapidly developing methods of scientific machine learning, including the use of symbolic regression, neural ordinary differential equations, and universal differential equations for model discovery (e.g., Martin et al, 2018;Guimerà et al, 2020;Rackauckas et al, 2020;Bonnaffé et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Valuable effort would therefore be expended in future work to consider the relationship of model flexibility to the parametric-and structural sensitivities of models when it comes to drawing inferences for population dynamics (e.g., Aldebert and Stouffer, 2018;Adamson and Morozov, 2020). Likewise, it would also be useful to clarify the relevance of model flexibility to the rapidly developing methods of scientific machine learning, including the use of symbolic regression, neural ordinary differential equations, and universal differential equations for model discovery (e.g., Martin et al, 2018;Guimerà et al, 2020;Rackauckas et al, 2020;Bonnaffé et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Since the inception of the Geber method by Hairston et al (2005) and Ellner et al (2011), a multiplicity of more sophisticated methods have flourished. These methods are based either on inferring parameters for dynamic models from data (Rudy et al 2017), on non-parametric approaches such as recurrent neural networks, or on hybrid approaches combining differential equations with neural networks (Bonnaffé et al 2021). Reviewing these methods is beyond the scope of this paper.…”
Section: Measuring the Trait Dependency Of Ecological Dynamics (Fig 1...mentioning
confidence: 99%
“…For instance, recently Dutta et al showed that NODE can generate the solutions for the various evolution problems of different fluid dynamics and further provide a promising potential to extrapolate [33]. Another attempt was to use NODE to learn ecological and evolutionary processes based on the time-series data generated by traditional ecological models [57]. Microbial communities are dynamical systems, in which microbes interact primarily through the metabolite consumption and production of byproduct metabolites [58, 34].…”
Section: Discussionmentioning
confidence: 99%